How to Inverse Exponential Functions
- 1). Take the logarithm of both sides of the equation. For example, taking the log of y = 2^x gives log(y) = log(2^x)
- 2). Simplify the right side using the rules that log(a^b) = b log(a). In the example, this gives log(y) = x log(2)
- 3). Simplify the entire expression by dividing as needed to get x alone on the right side of the equation. In the example, divide both sides by log(2), giving log(y)/log(2) = x.
- 4). Evaluate the logarithm in the denominator (bottom part) of the left side. This is the answer. In the example, log(2) = 0.301, giving log(y)/0.301 = x.
Source...